The Influence of Transformational Leadership and Work Culture on the Quality of Elementary School Learning - Eli Erlinawati; Bunyamin Bunyamin; I Made Sudana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the influence of transformational leadership and work culture on the quality of learning in elementary schools of the Baskara Sumirat Cluster, Tembalang District. This study uses a quantitative approach with an ex post facto design. Data collection is carried out through standardized questionnaires. The validity and reliability test was carried out using SPSS version 26. Data analysis includes descriptive statistics, key component analysis (PCA), and simple and multiple linear regressions. The results showed that transformational leadership had a significant influence of 60.4% on the quality of learning. Work culture contributed 35.4%, and simultaneously, the two variables explained 69.0% variability. The regression coefficient shows a greater influence of transformational leadership than work culture. This study highlights integrating leadership approaches and work culture in public elementary schools. This study reinforces the position of transformational leadership variables as a key factor that is more dominant than work culture, while providing an empirical data-based predictive model in the context of Indonesian basic education.